Circulating heart-type fatty acid-binding protein levels predict ventricular fibrillation in Brugada syndrome. Issue 3 (March 2016) - Daidoji, Hyuma; Arimoto, Takanori; Iwayama, Tadateru; Ishigaki, Daisuke; Hashimoto, Naoaki; Kumagai, Yu; Nishiyama, Satoshi; Takahashi, Hiroki; Shishido, Tetsuro; Miyamoto, Takuya; Watanabe, Tetsu; Kubota, Isao
Abstract: Background: The association between ongoing myocardial damage and outcomes in patients with Brugada syndrome who had received an implantable cardioverter-defibrillator (ICD) is unclear. Methods: Consecutive patients with Brugada syndrome ( n  = 31, 50 ± 13 years) who had received an ICD were prospectively enrolled. Minor myocardial membrane injury [heart-type fatty acid-binding protein (H-FABP) >2.4 ng/mL] and myofibrillar injury (troponin T >0.005 ng/mL) were defined using receiver operating characteristic curves. Patients were followed for a median period of 5 years to an endpoint of appropriate ICD shock. Results: Myocardial membrane injury (29%) and myofibrillar injury (26%) were similarly prevalent among patients with Brugada syndrome who had received ICDs. Appropriate ICD shocks occurred in 19% of patients during the follow-up period. Multivariate Cox regression analysis showed that serum H-FABP level >2.4 ng/mL, but not troponin T level, was an independent prognostic factor for appropriate ICD shock due to ventricular fibrillation [hazard ratio (HR) 25.2, 95% confidence interval (CI) 1.33–1686, p  = 0.03]. Conclusions: Evaluating myocardial damage using H-FABP may be a promising tool for predicting ventricular arrhythmia in patients with Brugada syndrome who have received ICDs.